2019
DOI: 10.1007/s12471-019-01315-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of patients with rheumatic MS after PBMV compared with MVS in a low-to-middle-income country

Abstract: IntroductionRheumatic mitral stenosis continues to be prevalent in developing countries, notably in endemic areas. Over the last few decades, percutaneous balloon mitral valvuloplasty (PBMV) has been established as a lower-cost alternative treatment for mitral stenosis (MS) in low-to-middle-income countries. PBMV has also been suggested to be an effective and safe alternative treatment modality. This study aims to analyse the survival of rheumatic MS patients treated with PBMV compared with those treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…21,22 Percutaneous balloon mitral valvuloplasty is a safe and effective management for rheumatic MS. It has excellent procedural success rate (defined by the composite endpoint of a final mitral valve area ≥1.5 cm 2 without mitral regurgitation [MR] of more than grade 2) of 90% to 95% [23][24][25] with good immediate 26 and long-term outcomes 21,22 ; event-free survival rate of 90% at 5-7 years, 27 61% to 96% at 10 years [28][29][30] and 43% to 79% at 15 years. 25,28 For this reason, PBMV is considered standard of care for selected patients with rheumatic MS with Wilkins score <8 and mild MR. 21,22 Wilkins score 31 is an echocardiographic method used to predict the success of PBMV in the setting of rheumatic MS.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Percutaneous balloon mitral valvuloplasty is a safe and effective management for rheumatic MS. It has excellent procedural success rate (defined by the composite endpoint of a final mitral valve area ≥1.5 cm 2 without mitral regurgitation [MR] of more than grade 2) of 90% to 95% [23][24][25] with good immediate 26 and long-term outcomes 21,22 ; event-free survival rate of 90% at 5-7 years, 27 61% to 96% at 10 years [28][29][30] and 43% to 79% at 15 years. 25,28 For this reason, PBMV is considered standard of care for selected patients with rheumatic MS with Wilkins score <8 and mild MR. 21,22 Wilkins score 31 is an echocardiographic method used to predict the success of PBMV in the setting of rheumatic MS.…”
Section: Introductionmentioning
confidence: 99%
“…(69.4%) were women, with a mean age of 39.3 -41.2 years, 18% had hypertension, and 8.1% complicated with DM type 2 [25].…”
Section: The Common Neglected Cvd In Lmicsmentioning
confidence: 99%
“…In Indonesia, the baseline characteristics were in agreement with the results from the REMEDY study [ 24 ]. Recent study by Ambari et al showed that among RHD patients with mitral stenosis in Indonesia, majority (69.4%) were women, with a mean age of 39.3 – 41.2 years, 18% had hypertension, and 8.1% complicated with DM type 2 [ 25 ].…”
Section: The Common Neglected Cvd In Lmicsmentioning
confidence: 99%
“…1 In the past 5 years, approximately 471 patients with rheumatic mitral stenosis were treated in our centre. 2 Treatments provided for RHD in advanced stages are relatively expensive for developing nations; thus, early detection and targeted treatment can greatly aid. 3 Mitral valve stenosis is the main presentation of RHD, commonly developing as a result of persistent or recurrent valvulitis with bicommissural fusion.…”
Section: Introductionmentioning
confidence: 99%